Prevalence of Café-au-Lait Spots in children with solid tumors - Anna Claudia Evangelista dos Santos; Benjamin Heck; Beatriz De Camargo; Fernando Regla Vargas (Genetics and Molecular Biology, 2016)
Abstract Cafe-au-lait maculae (CALM) are frequently observed in humans, and usually are present as a solitary spot. Multiple CALMs are present in a smaller fraction of the population and are usually associated with other congenital anomalies as part of many syndromes. Most of these syndromes carry an increased risk of cancer development. Previous studies have indicated that minor congenital anomalies may be more prevalent in children with cancer. We investigated the prevalence of CALMs in two samples of Brazilian patients with childhood solid tumors, totaling 307 individuals. Additionally, 176 school children without diagnosis of cancer, or of a cancer predisposing syndrome, were investigated for the presence of CALMs. The prevalence of solitary CALM was similar in both study groups (18% and 19%) and also in the group of children without cancer. Multiple CALMs were more frequently observed in one of the study groups (Z = 2.1). However, when both groups were analyzed together, the significance disappeared (Z = 1.5). The additional morphological abnormalities in children with multiple CALMs were analyzed and compared to the findings observed in the literature. The nosologic entities associated with CALMs are reviewed.